Permanent health education in a nursing technician course - Fernanda Juliano de Lima; Letícia Lopes Dorneles; Marta Cristiane Alves Pereira; José Renato Gatto Júnior; Fernanda dos Santos Nogueira de Góes; Rosangela Andrade Aukar de Camargo (SciELO, 2022)
ABSTRACT Objective: To assess the understandings of a pedagogical intervention on the Brazilian National Policy of Permanent Health Education targeted at secondary technical and vocational nursing students. Method: Applied, pedagogical intervention study conducted with twenty-three students of a secondary technical nursing course; questionnaires, focal group, and thematic content analysis were employed. Results: Intervention, collectively built by manager, nursing teachers, and researchers, is assessed to have led to a problematization of the concepts of education and continuing and permanent education. The following thematic categories emerged from the analysis: Prior knowledge of students and understandings of the classroom intervention; Relation between permanent education and educational welcome in health units; Ethics concerns and the articulation of care practice and theory; and Work process and approximations to permanent health education. Conclusion: The pedagogical intervention is assessed to have favored the critical reflection of the aspiring nursing technicians on permanent health education and the need for a collaborative pedagogical planning for aligning the health team's work process.